Comparative analysis of Phytophthora genomes reveals oomycete pathogenesis in crops - Gao, Rui-Fang; Wang, Jie-Yu; Liu, Ke-Wei; Yoshida, Kouki; Hsiao, Yu-Yun; Shi, Yi-Xiang; Tsai, Kun-Chan; Chen, You-Yi; Mitsuda, Nobutaka; Liang, Chieh-Kai; Wang, Zhi-Wen; Wang, Ying; et al. (Heliyon, 2021)
The oomycete genus Phytophthora includes devastating plant pathogens that are found in almost all ecosystems. We sequenced the genomes of two quarantined Phytophthora species–P. fragariae and P. rubi. Comparing these Phytophthora species and related genera allowed reconstruction of the phylogenetic relationships within the genus Phytophthora and revealed Phytophthora genomic features associated with infection and pathogenicity. We found that several hundred Phytophthora genes are putatively inherited from red algae, but Phytophthora does not have vestigial plastids originating from phototrophs. The horizontally-transferred Phytophthora genes are from abundant transposon activities that “transmit” exogenous genes to Phytophthora species and thus bring about the gene recombination possibility. Several expansion events of Phytophthora gene families associated with cell wall biogenesis can be used as mutational targets to elucidate gene function in pathogenic interactions with host plants. This work enhanced the understanding of Phytophthora evolution and will also be helpful for the design of phytopathological control strategies. Phytophthora; Genome; Phylogenetic; Pathogenicity; Horizontally gene transfer.